The Effect of International Exchange Programs on Improving The Accreditation of Higher Education (Study Analysis on Institute of Informatics and Business Darmajaya) - Rusdee Chemoh (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Study abroad at one of the partner universities of the educational institution is important. A student exchange program is a program in which students can study in other countries include not only study abroad, but also various international trips, language courses, and summer camps. They are aimed at gaining new knowledge in any field, as well as the practice of a foreign language. The methodology in this study was qualitative research using the descriptive-analytic method. The method was not only limited to data collection, but it also included data analysis and interpretation. Darmajaya as a private Institute provided some international programs for students and staff who wanted to go abroad. And by these programs, the institute had increased accreditation B in 2020 and it was able to achieve campus quality.Keywords: Exchange Programs, Internation Programs, Descriptive Analytic Method, Accreditation,High Education, IIB Darmajaya.